The Child Health Effects of Terrorism : Evidence from the Boko Haram Insurgency in Nigeria - Ekhator, Uche Eseosa (Taylor and Francis, 2019)
This study examines the effect of terrorism on height-for-age z-scores, weight-for-age z-scores, weight-for-height z-scores, stunting, and wasting. Using the Boko Haram Insurgency, it compares outcomes in Boko Haram high-active and low-active areas. A difference-in-difference and regression model identifies the extensive and intensive margin effects respectively. The study uses data from the Nigeria Demographic and Health Survey and the Global Terrorism Database. The results suggest that the Boko Haram Insurgency reduces weight-for-age and weight-for-height z-scores and increases the probability of wasting. The evidence suggests that policies targeting healthcare services may mitigate the long-term impacts of the Boko Haram Insurgency on human capital production.